2008
DOI: 10.1086/529436
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Joint Prosthesis Infection in Accordance with Current Recommendations Improves Outcome

Abstract: Our study demonstrates the value of current treatment recommendations. Inappropriate choice of conservative surgical strategies (such as debridement and retention) and inadequate antibiotic treatment are associated with failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 17 publications
3
60
2
2
Order By: Relevance
“…These guidelines have not yet been prospectively validated and were based on only one randomized study, various cohort studies, expert opinion, and animal experiments [1]. However, Betsch et al and Giulieri et al demonstrated the value of current recommendations in cohort studies including patients infected with a broad range of pathogens [3,4]. An inappropriate choice of conservative surgical strategies and inadequate antibiotic treatments were both associated with failure during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These guidelines have not yet been prospectively validated and were based on only one randomized study, various cohort studies, expert opinion, and animal experiments [1]. However, Betsch et al and Giulieri et al demonstrated the value of current recommendations in cohort studies including patients infected with a broad range of pathogens [3,4]. An inappropriate choice of conservative surgical strategies and inadequate antibiotic treatments were both associated with failure during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci (S. aureus and coagulase-negative staphylococci) are the most frequent causes of implant-associated infections [1][2][3][4][5]. These bacteria have the ability to modify their phenotype in order to persist in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance with these criteria is important, because it significantly improves the chance of cure (Giulieri et al 2004, Betsch et al 2008.…”
mentioning
confidence: 99%
“…Betsch ve arkadaşlarının yaptığı çalışmada tek aşamalı ve iki aşamalı deği-şimin başarı oranları %0 (0/4) ve %65 (33/51) olarak bulunurken, Giuleri ve arkadaşlarının yaptı-ğı bir çalışmada ise tek aşamalı değişimin başarı oranı %94 (15/16) iken, iki aşamalı değişimde bu oran %90 (28/31) olarak bulunmuştur [15] .…”
Section: Tablo 4 Operasyon Sonrası Metisiline Dirençliunclassified